Profitability of corn production in agroecological and conventional systems in two communities of Tlaxcala - Ayala Garay, Alma Velia; Hernández Vázquez, Benjamín (Agricultura, Sociedad y Desarrollo, 2023)
The objective of this study was to conduct a comparative study of profitability between glyphosate-free corn production in the agroecological lighthouse “Grupo Vicente Guerrero”, Españita, Tlaxcala and conventional Creole corn production in Huamantla, Tlaxcala. To calculate the profitability, a survey was applied to 20 producers who belong to the lighthouse and 20 to the ejido of Huamantla. The producers from Vicente Guerrero are characterized by their trajectory in agroecological agriculture and the promotion of alternative technologies; they manage corn as a poly-crop, associated with bean, squash and weeds, agro-ecosystem known as milpa. This management demands a greater number of people in the workforce to execute the tasks of farming, substituted in conventional management with the use of herbicides and other agrichemicals. In the calculation of profitability, the benefit cost B/C rate in Vicente Guerrero was 1.24, which is profitable for the producer; meanwhile, the opposite was seen in producers from Huamantla, with a B/C rate of 0.88, that is, negative, so this production is not profitable. The establishment of lighthouses ensures the agroecological management of corn which, in addition to being profitable, contributes to the decrease in risks and damages to the population’s health.